A new species of Upeneus (Perciformes: Mullidae) from southern Japan - Yamashita, Masahiro; Golani, Daniel; Motomura, Hiroyuki (Zootaxa, 2011)
A new species of goatfish, Upeneus itoui, is described on the basis of 67 specimens collected from southern Japan at depths of less than 40 m. Upeneus itoui is most similar to the western Indian Ocean species, U. pori. The caudal-fin color pattern in fresh and preserved specimens of the two species is identical. However, U. itoui differs from U. pori in having less head and body depths, wider barbels, and a lower count of gill rakers.